2002
DOI: 10.1046/j.1365-2141.2002.03895.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow transplantation in the treatment of refractory systemic sclerosis: early results from a French multicentre phase I–II study

Abstract: Summary. Haematopoietic stem cell transplantation (HSCT) has been proposed for refractory autoimmune diseases, including systemic sclerosis (SSc). A sequential Bayesian phase I-II clinical trial was conducted in SSc patients to assess the feasibility, the tolerance and the efficacy of autologous HSCT. Peripheral blood stem cells (PBSC) were collected using cyclophosphamide (4 g/m 2 ) and recombinant human granulocyte colony-stimulating factor (5 lg/kg/d) and reinfused after positive CD34 + selection. Condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
9

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 40 publications
1
94
0
9
Order By: Relevance
“…These data extend preliminary results from early pilot and single disease focused studies. [10][11][12][13][14][15] They confirm the concept of dose intensification as a therapeutic strategy. Increasing intensity reduces the risk of disease progression.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These data extend preliminary results from early pilot and single disease focused studies. [10][11][12][13][14][15] They confirm the concept of dose intensification as a therapeutic strategy. Increasing intensity reduces the risk of disease progression.…”
Section: Discussionmentioning
confidence: 61%
“…9 Pilot series have established and defined response criteria. [10][11][12][13][14][15] Insufficient data were as yet available to assess factors associated with outcome; mechanisms of action remained hypothetical. The present analysis documents the feasibility and efficacy of the procedure, clarifies the role of dose intensification and forms the basis for the ongoing prospective randomized phase III trials.…”
Section: Discussionmentioning
confidence: 99%
“…Improved skin score and quality of life and at least stabilization of lung function were consistently reported in early phase II trials. [4][5][6][7][8] Recently, the phase II ASSIST 9 and the larger phase III ASTIS 10 prospective randomized trials showed better survival rates and improved skin, lung and functional status in patients treated with AHSCT as compared with monthly IV cyclophosphamide. Still, the transplant-related mortality reaching 10% and disease-progression rates of around 20-30% after AHSCT indicate that further improvements are still warranted.…”
Section: Introductionmentioning
confidence: 99%
“…[57][58][59][60][61][62] TBI is not an essential agent and can be easily replaced with agents that have similar or higher immune ablative potential but without myeloablation, acute and chronic exacerbation of vascular injury, risk of damage to organ stem cell compartments, hindrance of repair mechanisms, and compared to TBI minimal risk of late malignancies.…”
Section: The Future Of Hsct For Sclerodermamentioning
confidence: 99%